192 Dietary β-mannanase supplementation improved growth and health of nursery pigs fed high soybean meal diet. (7th December 2018) - Qiao, Y; Zhu, X; Zhai, L; Payne, R; Li, T
Abstract: One hundred Landrace × Yorkshire barrows (BW Mean 9.49 kg, SD 1.18 kg) were used in a thirty-day 2 × 2 factorial RCBD trial to study the effects of soybean meal (SBM) and β-mannanase (Hemicell XT). Treatments were SBM (220 and 370 g/kg, making dietary soluble β-mannan to 2420 and 4070 ppm, respectively) and β-mannanase (0 and 200 mg/kg). Diets were isocaloric (3200 kcal/kg ME) and equal in SID Lys (12.5 g/kg). Pigs were penned individually. Feed intake and fecal condition score (FCS) were recorded daily. On Day 0, 14 and 30, all were weighed and nine per treatment were sampled for precaval vein blood to measure serum galactomannan and haptoglobin. Data were analyzed with Proc Mixed of SAS. In Day 0–14 and Day 14–30, ADFI, ADG and end BW were affected by SBM × β-mannanase interaction (P<0.0277). In Day 14–30, SBM decreased ADFI (P<0.001) and ADG (P=0.0370) and β-mannanase increased them (P<0.0103). From Day 0–30, ADFI, ADG and G/F were decreased by SBM (P<0.0181), increased by β-mannanase (P<0.0344) and affected by SBM × β-mannanase (P<0.0051). In Day 0–14, Day 14–30 and Day 0–30, FCS was increased by SBM (P<0.0001) and affected by SBM × β-mannanase (P<0.0002). В-mannanase decreased FCS in Day 14–30 and Day 0–30 (P<0.0001). Runting pig occurrence was increased by SBM (P=0.0075), decreased by β-mannanase (P=0.0075) and affected by SBM × β-mannanase (P=0.0022). Serum galactomannan was decreased by SBM on Day 14 (P=0.0465) and Day 30 (P=0.0002), increased by β-mannanase on Day 30 (P=0.0022) and affected by SBM × β-mannanase on Day 14 and Day 30 (P<0.0003). Treatments had no effect on haptoglobin. Multiple SBM × β-mannanase indicated treatment interdependence to show effects. High SBM without β-mannanase damaged health and growth. B-mannanase supplementation alleviated the harms and restored growth and health to levels of low SBM diets.